The prevalence of undetected second distal canals in endodontic-treated mandibular first molars: A histological and cone beam computed tomography study - Al-Huwaizi, Hussain. F.; Mutlag, Labeeb Sabbar (Iraqi Journal of Science, 2025)
The mandibular first molar that has undergone endodontic treatment (ETMFM) may contain an additional canal that often goes unnoticed, known as the undetected second distal canal (USDC). While radiography is commonly used to identify the USDC in ETMFMs, its actual occurrence rate might differ when examined through histological methods. The prevalence of this canal was evaluated histologically through laboratory analysis and radiographically through cone beam computed tomography (CBCT). This study included 24 ETMFM from a total of 372 extracted mandibular first molars (MFM) from 372 Iraqi patients, which were collected from several private dental clinics in Baghdad city during 2022–2023. The extra canals, accounting for 6.45% of the total samples, is divided into two groups based on sex. All the teeth were examined using a single CBCT device, and then they were histologically prepared, sectioned, and observed under a stereomicroscope. The images were evaluated for the presence of the canals, and the results were statistically analyzed using the chi-square test and the Fisher exact test. The comparison was considered statistically significant at p<0.05. The prevalence rate of the canals was 13 teeth (54.16%) based on CBCT, while 18 teeth (75% histologically) had a sex distribution of 6/12 teeth (33.33% for males and 66.66% for females). In terms of the level of sectioning, 74.44% of all sections had USDC, with the lowest being 7.46% at level 1 (apical level) and 19.4% at level 2. The prevalence rates of the USDC were found to be high in ETMFM clinically, higher in the histological study than in the CBCT study, higher in females than in males, and higher in the middle sectioning levels than at the extremes, all of which showed no statistically significant difference. Consequently, in suspicious cases, additional examinations are required to confirm the existence or absence of these canals, as they are regarded as a contributing factor in the failure and tooth extraction after endodontic treatment in ETMFM.